Unjuk Kerja Panel Surya Kapasitas 50 Wp Terhadap Perubahan Intensitas Cahaya Matahari - Yusuf Rizal Fauzi (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2019)
This research was conducted to determine the performance of solar panels with a capacity of 50 Wp of the sun intensity fluctuations it receives. This research was conducted by measuring sunlight on the surface area of solar cells using Luxmeter. Then at the same time the current and voltage data are collected. This research was conducted for 5 days starting from 6am to 6pm local time. From the calculation results obtained an average output power of 7.356809231 Watt and in a day can produce 95.63852 Wh.